2010
DOI: 10.1007/s00408-010-9241-8
|View full text |Cite
|
Sign up to set email alerts
|

Nontuberculous Mycobacterial Lung Infections in Ontario, Canada: Clinical and Microbiological Characteristics

Abstract: Women comprised a small majority with disease. Nodular bronchiectasis in women was most common, but significant proportions of each gender with each radiographic type were observed. NTM isolation, particularly MAC, was frequently associated with disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
36
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 37 publications
5
36
0
Order By: Relevance
“…Among Oregon residents with PNTM, only 16% had bronchiectasis (42), and in a study of non-AIDS PNTM-associated hospitalizations, 15% also had bronchiectasis (5), although these studies both included patients less than 65 years old. Among patients in Canada more than 56 years old meeting ATS criteria for NTM infection, 62% had nodular bronchiectasis (43). Although bronchiectasis may increase susceptibility to NTM infection, infection with NTM likely also exacerbates bronchiectasis.…”
Section: Discussionmentioning
confidence: 99%
“…Among Oregon residents with PNTM, only 16% had bronchiectasis (42), and in a study of non-AIDS PNTM-associated hospitalizations, 15% also had bronchiectasis (5), although these studies both included patients less than 65 years old. Among patients in Canada more than 56 years old meeting ATS criteria for NTM infection, 62% had nodular bronchiectasis (43). Although bronchiectasis may increase susceptibility to NTM infection, infection with NTM likely also exacerbates bronchiectasis.…”
Section: Discussionmentioning
confidence: 99%
“…Studies from Ontario, Oregon and Denmark showed that both populations look strikingly similar in terms of socio-demographic and clinical characteristics and both have poor survival. 24,42,43 Among Danish patients (mean age about 60 years), the 5-year mortality was 33.5% in NTM colonization and 40.1% in NTM disease with no statistical difference. 24 While NTM species and disease severity contribute to mortality, 44,45 deaths are predominately caused by comorbidities rather than the NTM infection.…”
Section: Discussionmentioning
confidence: 99%
“…Still, PPV of stricter microbiologic criteria was considerably higher when compared to ATS/IDSA microbiologic criteria (93.3% vs. 59.8%). 4,17,18 Thus, to prevent unwarranted diagnoses and treatment of NTM disease, as well as unnecessary diagnostic delay, it could be helpful to use separate, more stringent criteria for species of low relevance, and less stringent criteria for species considered to be of high clinical relevance in the local setting. This aspect should be covered in the upcoming diagnostic criteria.…”
Section: Criteria Correlationmentioning
confidence: 99%